Question
upstudy study bank question image url

\( \sum _ { k = 1 } ^ { m } 3 ( 2 ) ^ { k - 1 } = 93 \)

Ask by Peterson Hammond. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( m = 5 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Mind Expander

To solve the equation \( \sum _ { k = 1 } ^ { m } 3 ( 2 ) ^ { k - 1 } = 93 \), we can recognize that this is a geometric series. The sum of a geometric series can be calculated using the formula for the sum of the first \( n \) terms: \[ S_n = a \frac{1 - r^n}{1 - r} \] where \( a \) is the first term and \( r \) is the common ratio. Here, \( a = 3 \) and \( r = 2 \). Therefore, we can rewrite the sum as: \[ S_m = 3 \frac{1 - 2^m}{1 - 2} = 3(1 - 2^m)(-1) = 3(2^m - 1) \] Setting this equal to 93 gives: \[ 3(2^m - 1) = 93 \] Dividing both sides by 3, we obtain: \[ 2^m - 1 = 31 \] Adding 1 to both sides leads to: \[ 2^m = 32 \] Since \( 32 \) can be expressed as \( 2^5 \), we find that: \[ m = 5 \] Thus, the value of \( m \) is \( 5 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy